Genetic diversity management of sculpin (Cottus spp.) and brown trout (Salmo trutta) in the Palatinate Forest-North Vosges Biosphere Reserve - Schmidt Thomas; Cairault Alban; Schulz Ralf (Knowledge and Management of Aquatic Ecosystems, 2023)
Protected areas can make an important contribution to the conservation of genetic diversity in the current biodiversity crisis. We have examined two representative freshwater fish taxa, Cottus spp. and Salmo trutta, in 15 midmountain headwaters of the Franco-German Palatinate Forest-North Vosges Biosphere Reserve in Central Europe to facilitate freshwater genetic diversity protection. Population genetic analyses of microsatellites and mtDNA showed lower genetic diversity, but distinctly differentiated genetic structure in Cottus spp., and higher diversity, but less differentiated structure in Salmo trutta. Phylogenetic analyses of mtDNA designated most sculpin to Cottus gobio, but also identified the first known population of Cottus rhenanus in the region. In addition to species-specific recommendations, we derived stream-specific guidance in an attempt to make optimal use of the combined genetic information on both taxa for habitat-oriented management prioritization and improved conservation of freshwater genetic diversity.